Protective efficacy of a SARS-CoV-2 DNA vaccine in wild-type and immunosuppressed Syrian hamsters - Rebecca L. Brocato (Nature Portfolio, 2021)
Abstract A worldwide effort to counter the COVID-19 pandemic has resulted in hundreds of candidate vaccines moving through various stages of research and development, including several vaccines in phase 1, 2 and 3 clinical trials. A relatively small number of these vaccines have been evaluated in SARS-CoV-2 disease models, and fewer in a severe disease model. Here, a SARS-CoV-2 DNA targeting the spike protein and delivered by jet injection, nCoV-S(JET), elicited neutralizing antibodies in hamsters and was protective in both wild-type and transiently immunosuppressed hamster models. This study highlights the DNA vaccine, nCoV-S(JET), we developed has a great potential to move to next stage of preclinical studies, and it also demonstrates that the transiently-immunosuppressed Syrian hamsters, which recapitulate severe and prolonged COVID-19 disease, can be used for preclinical evaluation of the protective efficacy of spike-based COVID-19 vaccines.